(untitled) (Baghdad Science Journal, 2020)
This research deals with increasing the hardening and insulating the petroleum pipes against the conditions and erosion of different environments. So, basic material of epoxy has been mixed with Ceramic Nano Zirconia reinforcement material 35 nm with the percentages (0,1,2,3,4,5) %, whereas the paint basis of broken petroleum pipes was used to paint on it, then it was cut into dimensions (2 cm. × 2 cm.) and 0.3cm high. After the paint and percentages are completed, the samples were immersed into the paint. Then, the micro-hardness was checked according to Vickers method and thermal inspection of paint, which contained (Thermal conduction, thermal flux and Thermal diffusivity), the density of the painted samples was calculated,. The results of the research indicate that the concentration (5%ZrO2) gives the best results that the hardness of this concentration reached to (92 Hv). By contrast, the thermal conduction was continued at a insulation limit (2.4 W/m.K). The thermal diffusivity was (1.16 mm2/sec.), the thermal flux reached to (70.4 w.s 1/2/m2.K) and the density at the same percentage was (4.87 g/m3). This means that there is a linear proportionality and development with increasing in the percentage of Nano Zirconia additive to epoxy.